Efeitos da adenosina na toxicidade da radiação ionizante em larvas de zebrafish (Danio rerio) - Cruz, Fernanda Fernandes (2020)
Ionizing radiation (gamma rays and x-rays) is useful in industrial applications and especially in medicine for diagnosis and therapy. Despite advances in its use, radiotherapy can cause adverse effects, which as a result of an exacerbated inflammation evolves into a toxic scenario that limits the success of therapy. Moreover, environmental, acidental or occupational exposure are also of great concern since they can cause serious health consequences such as immune system disorders, cardiovascular disease, progeny malformations, genetic mutations and cancer. Adenosine is an ATP metabolite formed from the AMP breakdown by the enzyme CD73, and is transformed into inosine by ADA. This nucleoside exerts its actions by binding to the four P1 receptor subtypes: A1, A2A, A2B and A3. Adenosinergic signaling is involved in several physiological and pathological functions. In response to injury, extracellular adenosine levels increase to protect tissues from perpetual inflammation and to limit the immune response. Due to its protective effects, adenosine is known as a "retaliatory metabolite", promoting effects on imune cell activity, release of inflammatory cytokines and growth factors, oxidative defenses and tissue remodeling. Zebrafish is a freshwater teleost used as a model for various human diseases. It is suitable for toxicology and pharmacology studies, and has been adopted to evaluate the toxic effects of ionizing radiation and in the search for radioprotectors. In this context, this study aimed to evaluate the involvement of adenosine in the toxicity of ionizing radiation in zebrafish larvae. Zebrafish embryos with 24 hpf were exposed to different doses of gamma radiation and after seven days, a series of toxicological parameters were evaluated. The embryos/larvae showed significant changes in heart rate, hatching time, morphology and locomotor activity. The 10 Gy dose of gamma radiation induced a decrease in CD73 and ADA enzyme activities, indicating a decrease in extracellular adenosine levels. In addition, A2B receptor gene expression was decreased. These results suggest that there is a relation between the deleterious effects promoted by ionizing radiation and a decrease in adenosinergic signaling. Subsequently, the embryos were pre-treated with adenosine at concentrations of 1, 10 and 100 μM, 30 minutes before exposure to 15 Gy of gamma radiation, in order to evaluate the adenosine radioprotective effects. Toxicological parameters related to larval development were enhanced by adenosine treatment, especially at 100 μM. However, adenosine reversed the oxidative stress (CAT and GSH) promoted by radiation and normalized the gene expression of inflammation and tissue remodeling markers (TNF; HIF-1α; VEGFR2; IL-6; IL-8; TGFβ1a; TGFβ1b). A2A2 and A2B receptors appear to exert greater participation in the cytoprotection processes presented by adenosine treatment. Consequently, the results indicate that adenosine is involved in the toxicity of ionizing radiation and the modulation of adenosinergic signaling may have benefits in the discovery of radioprotection mechanisms and in the management of inflammation and toxicity triggered by radiation exposure.